Neurofunctional correlates of emotional dysregulation in adolescent Crohn’s disease: a resting-state fMRI preliminary investigation - Liu, Ao; Huang, Mengting; Deng, Xiaoling; Huang, Shuo; Xu, Keshu (Frontiers in Neuroscience, 2025)
BackgroundThis study aimed to characterize the relationship between abnormal intrinsic brain function with emotional symptoms in adolescent Crohn’s disease (CD) patients through resting-state functional magnetic resonance imaging (rs-fMRI).MethodsForty adolescent CD patient and 53 healthy controls (HCs) were recruited and completed standardized assessments including the Inflammatory Bowel Disease Questionnaire (IBDQ), Symptom Checklist-90 (SCL-90), Social Support Rating Scale (SSRS), and rs-fMRI scans. Compared the intrinsic brain function between groups using amplitude of low-frequency fluctuations (ALFF) and fractional ALFF (fALFF). Subsequent correlation analyses examined relationships between neuroimaging findings clinical indicators, and psychometric measures.ResultsAdolescent CD patients demonstrated significantly lower IBDQ and SSRS scores but higher SCL-90 scores. ALFF abnormalities localized to left superior/inferior temporal gyri, and left precuneus gyrus, while fALFF alterations involved left calcarine fissure and surrounding cortex, Vermis, and left superior frontal gyrus medial. Notably, functional connectivity (FC) of these regions were also changed. Critically, seed-based FC analysis revealed enhanced coupling between left precuneus and both the left superior temporal gyrus and left inferior temporal gyrus and between left medial superior frontal gyrus, left calcarine cortex, and cerebellar vermis, suggesting disease-specific hyperconnectivity in sensory-cognitive networks. Meanwhile, the ALFF in left inferior temporal gyrus was negatively correlated with obsessive compulsive (r = −0.348, p = 0.028), depression (r = −0.344, p = 0.003), and anxiety (r = −0.388, p = 0.013), but positively associated with serum albumin (r = 0.338, p = 0.033). The fALFF in vermis showed positive association with interpersonal sensitivity (r = 0.316, p = 0.047), depression (r = 0.336, p = 0.020), paranoid (r = 0.314, p = 0.049), psychoticism (r = 0.359, p = 0.023) in adolescent CD patients.ConclusionThese findings provide new insights into the neurobiological basis of emotional symptoms in adolescent CD patients, highlighting altered activity in temporal, frontal, and cerebellar regions.